2019
DOI: 10.1093/ndt/gfz235
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of physical activity across kidney disease stages: an observational multicentre study

Abstract: Background People with chronic kidney disease (CKD) report high levels of physical inactivity, a major modifiable risk factor for morbidity and mortality. Understanding the biological, psychosocial and demographic causes of physical activity behaviour is essential for the development and improvement of potential health interventions and promotional initiatives. This study investigated the prevalence of physical inactivity and determined individual correlates of this behaviour in a large sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 47 publications
4
84
0
Order By: Relevance
“…From the stage of disease perspective, this study also found that the patients' exercise self-e cacy gradually decreased as the progress of the renal function. A similar result was found by Wilkinson et al, whose study used the General Practice Physical Activity Questionnaire to evaluate CKD patients' physical activity, the result showed that 34% patients in CKD stage 1-2 were su ciently active, but decreased from stage 3 (17% active), through to stage 4-5 (11% active), and reaching a nadir in patients received dialysis (only 6%-8%) [20]. It is perhaps unsurprising that physical activity levels worsen as CKD progresses given the increasing symptom burden and reductions in physical function aggravated by anemia, metabolic acidosis, in ammation, and malnutrition [23].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…From the stage of disease perspective, this study also found that the patients' exercise self-e cacy gradually decreased as the progress of the renal function. A similar result was found by Wilkinson et al, whose study used the General Practice Physical Activity Questionnaire to evaluate CKD patients' physical activity, the result showed that 34% patients in CKD stage 1-2 were su ciently active, but decreased from stage 3 (17% active), through to stage 4-5 (11% active), and reaching a nadir in patients received dialysis (only 6%-8%) [20]. It is perhaps unsurprising that physical activity levels worsen as CKD progresses given the increasing symptom burden and reductions in physical function aggravated by anemia, metabolic acidosis, in ammation, and malnutrition [23].…”
Section: Discussionsupporting
confidence: 80%
“…Epidemiological investigations have shown that the level of physical activity in the population decreases with age [18], we found the score of ESES in elderly patients (≥ 65 years) was lower than that of nonelderly patients (< 65 years) probably because the muscle strength, muscle endurance, and motivation of elderly patients are worse than those of non-elderly patients, besides, decreased renal function exacerbates these factors [19]. Recently, a large cross-sectional study from the United Kingdom, nondialysis patients with CKD among males were approximately three times more likely to engage in physical activity than females [20]. Similar results were observed in the present study, which showed that the male in the study scored higher than female.…”
Section: Discussionmentioning
confidence: 99%
“…Our result can be explained by the fact that hemodialysis patients are prone to have sedentary lifestyles and to have low levels of physical activity [5,6]. Other studies also reported that decreased physical activity was associated with reduced walking speed in hemodialysis patients [7,8].…”
Section: Potential Mechanismmentioning
confidence: 53%
“…Our result can be explained by the fact that hemodialysis patients are prone to have sedentary lifestyles and to have low levels of physical activity. 7,8 Other studies also reported that decreased physical activity was associated with reduced walking speed in hemodialysis patients. 9,10 We can speculate that social frailty such as a reduced frequency of going out and social visits with friends, reduces walking speed by limiting patients' opportunities to engage in physical activity.…”
Section: Potential Mechanismmentioning
confidence: 99%